2005
DOI: 10.1007/s00383-005-1583-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Connexin 43 in the hearts of rat embryos exposed to nitrofen and effects of vitamin A on it

Abstract: Rats with experimental congenital diaphragmatic hernia (CDH) have heart hypoplasia and conotruncal and great vessel malformations that are likely related to disturbed neural crest developmental control. Neural crest cells communicate through intercellular gap junctions whose main protein is Connexin 43 (Cx43). The migration and participation of neural crest cells in heart development is likely influenced by this protein which might be also directly involved in myocardial development. Vitamin A is beneficial fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…As the promoter region of Cx43 contains multiple consensus sequences for AP1 and Sp1 binding [75,76], low intracellular Zn level has been associated with increased AP1-DNA binding activity in other cell types [77,78]. Of note, rat fetuses exposed to the herbicide nitrofen exhibit outflow tract and great vessel defects and show a transient increased expression of Cx43 in the heart [79]. It has also been suggested that the cardiac outflow defects observed after hyperhomocysteinemia can be in part due to elevated Cx43 levels [80].…”
Section: Discussionmentioning
confidence: 98%
“…As the promoter region of Cx43 contains multiple consensus sequences for AP1 and Sp1 binding [75,76], low intracellular Zn level has been associated with increased AP1-DNA binding activity in other cell types [77,78]. Of note, rat fetuses exposed to the herbicide nitrofen exhibit outflow tract and great vessel defects and show a transient increased expression of Cx43 in the heart [79]. It has also been suggested that the cardiac outflow defects observed after hyperhomocysteinemia can be in part due to elevated Cx43 levels [80].…”
Section: Discussionmentioning
confidence: 98%
“…It has been recently revealed that molecular signalling involved in this superfamily is disrupted in murine hypoplastic lungs leading to reduced number of alveoli and abnormal alveolar structure, which may be attributed to downregulation of RARs [32]. Furthermore, it has been recently reported that either gain or loss of Cx43 function is involved in the pathogenesis of cardiac malformations in experimental CDH and that Vitamin A administration can rescue them [19,23,33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that lungs of Cx43 knockout mice display features of severe PH, which are also seen in the nitrofen-induced PH [20]. Furthermore, in vitro studies have demonstrated that retinoids increase Cx43 expression in rodents as well as in humans [21][22][23][24].…”
mentioning
confidence: 96%
“…Those include endothelin-1, angiotensin-II, thyroid hormones, AAP10 and nitrofen [27][28][29][30]. As to the therapeutic challenge to ameliorate arrhythmogenic substrates, however, all of these procedures have significant limitations in their clinical feasibility because of their low efficiency, undesirable cardiovascular and other side effects.…”
Section: What Other Methods Could Be Considered To Achieve Similar Rementioning
confidence: 98%